Polyamic acid composition, polyimide composition, metal-clad laminate and circuit board
The polyamic acid composition, incorporating α-alumina fine particles and biphenyl-derived residues, addresses the challenge of improving thermal conductivity in polyimide insulating layers without compromising dielectric properties or adhesion, thereby enhancing the performance of flexible printed wiring boards.
Patent Information
- Application Number
- JP2020215639
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-24
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2040-12-24
AI Technical Summary
Existing polyamic acid compositions used for forming polyimide insulating layers in flexible printed wiring boards lack specific descriptions for thermally conductive fillers, leading to inadequate thermal conductivity without compromising the low dielectric loss tangent and coefficient of thermal expansion requirements.
A polyamic acid composition is developed containing α-alumina fine particles as thermally conductive fillers, along with diamine and acid anhydride residues derived from components with biphenyl structures, to achieve a highly ordered crystalline structure, improved thermal conductivity, and maintained adhesion to metal layers.
The polyamic acid composition effectively enhances thermal conductivity without increasing the dielectric loss tangent, while maintaining a low coefficient of thermal expansion and ensuring good adhesion to metal layers, making it suitable for high-density mounting and high-frequency signal transmission applications.
Smart Images

Figure 0007648377000001 
Figure 0007648377000002 
Figure 0007648377000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyamic acid composition which is a precursor of a polyimide composition useful as an insulating layer material for circuit boards such as flexible printed wiring boards, a polyimide composition which is an imidized product thereof, a metal-clad laminate, and a circuit board. [Background technology]
[0002] In order to use a flexible circuit board (FPC) made from a metal-clad laminate having a basic structure in which a polyimide insulating layer made by imidizing polyamic acid is laminated on a copper foil for high-frequency transmission, it is required that the polyimide insulating layer has a low dielectric tangent, and also that the thermal expansion coefficient is within a predetermined range from the viewpoint of shape stability. In addition, in order to use an FPC for high-density mounting, it is effective to use a copper foil with a small surface roughness in order to accommodate fine processing of wiring and to suppress diffuse reflection of light on the surface of the polyimide insulating layer in the area where the copper foil is removed by etching, and it is known that the use of a copper foil with a small surface roughness can also suppress the increase in resistance of signal wiring due to the so-called skin effect. Therefore, attempts have been made to manufacture an FPC from a metal-clad laminate in which a copper foil with a relatively low surface roughness is laminated on a polyimide insulating layer having a thermal expansion coefficient within a predetermined range and a small dielectric tangent.
[0003] However, if a copper foil with a small surface roughness is used for the FPC, there is a concern that the adhesion between the polyimide insulating layer and the copper foil may be impaired.
[0004] In consideration of such problems, a polyamic acid obtained by reacting a specific diamino aromatic compound with a tetracarboxylic dianhydride has been proposed as a precursor for forming a polyimide having a low dielectric tangent and exhibiting good adhesion even to a metal layer with a small surface roughness (Patent Document 1).
[0005] Incidentally, in recent years, with the trend toward high-density packaging of electronic devices, heat generation from integrated circuits has become a problem, and there is a demand for the polyimide insulating layer of FPCs to exhibit good thermal conductivity. Thus, it has been considered to incorporate a known thermally conductive filler into the polyamic acid of Patent Document 1, which is a precursor of polyimide. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] WO2017 / 159274A1 Summary of the Invention [Problem to be solved by the invention]
[0007] However, Patent Document 1 does not provide any specific description regarding thermally conductive fillers, and does not recognize the problem of improving the thermal conductivity of polyimide. In addition, although it is expected that polyimides formed from polyamic acid compositions in which thermally conductive fillers are dispersed and mixed in polyamic acid will have improved thermal conductivity, Patent Document 1 does not provide any specific description that the polyimides exhibit the same "low dielectric tangent" and "coefficient of thermal expansion" as polyimides formed from polyamic acids that do not contain thermally conductive fillers, and further, that they have good "adhesion to metal layers."
[0008] An object of the present invention is to provide a polyimide formed from a polyamic acid composition in which a thermally conductive filler is dispersed and mixed in polyamic acid, with a desired thermal conductivity without increasing the dielectric tangent value, and further with a desired "coefficient of thermal expansion" and good "adhesion to a metal layer". [Means for solving the problem]
[0009] The present inventors have found that by adopting a residue having a biphenyl structure having a mesogen skeleton that easily self-aligns at a certain ratio as the diamine residue and the acid anhydride residue constituting the polyamic acid, a highly ordered crystalline structure can be realized without significantly decreasing the adhesion to a metal layer such as a copper foil, and the polyimide can have a low dielectric tangent, and furthermore, by reducing phonon scattering, the thermal conductivity can be increased. The present inventors have also found that by adopting α-alumina fine particles having high crystallinity and low dielectric tangent within a predetermined particle size range as the thermal conductive filler, the thermal conductivity can be improved without increasing the dielectric tangent of the polyimide containing the α-alumina fine particles, and furthermore, by dispersing the α-alumina fine particles in a predetermined amount range in the polyamic acid, the aggregation of the α-alumina fine particles can be suppressed, and good coatability can be imparted to the polyamic acid composition. Based on these findings, the present inventors have completed the present invention.
[0010] That is, the present invention provides a polyamic acid composition containing a polyamic acid having a diamine residue derived from a diamine component and an acid anhydride residue derived from a tetracarboxylic dianhydride component, and α-alumina fine particles, the content of the α-alumina fine particles in the polyamic acid composition is 20 to 80 parts by volume per 100 parts by volume of the polyamic acid; Average particle size of α-alumina particles D 50 is 2 μm or more and 10 μm or less (wherein the average particle diameter D 50 is the average particle size at which the cumulative value in the frequency distribution curve obtained by volume-based particle size distribution measurement using the laser diffraction scattering method is 50%, the diamine residue derived from the diamine component contains 10 mol % or more of a diamine residue having a biphenyl structure, The acid anhydride residue derived from the tetracarboxylic dianhydride component contains 50 mol % or more of an acid anhydride residue having a biphenyl structure. A polyamic acid composition is provided.
[0011] The present invention also provides a polyimide composition comprising a polyimide having a diamine residue derived from a diamine component and an acid anhydride residue derived from a tetracarboxylic dianhydride component, and α-alumina fine particles, the content of the α-alumina fine particles in the polyimide composition is 20 to 80 parts by volume per 100 parts by volume of polyimide; Average particle size of α-alumina particles D 50 is 2 μm or more and 10 μm or less (wherein the average particle diameter D 50 is the average particle size at which the cumulative value in the frequency distribution curve obtained by volume-based particle size distribution measurement using the laser diffraction scattering method is 50%, the diamine residue derived from the diamine component contains 10 mol % or more of a diamine residue having a biphenyl structure, The acid anhydride residue derived from the tetracarboxylic dianhydride component contains 50 mol % or more of an acid anhydride residue having a biphenyl structure. A polyimide composition is provided.
[0012] The present invention further provides a metal-clad laminate comprising a metal layer and a polyimide insulating layer laminated together, in which the polyimide insulating layer is formed from the polyimide composition of the present invention, and a circuit board in which the metal layer of the metal-clad laminate is processed into wiring. Effect of the Invention
[0013] The polyamic acid composition of the present invention adopts a certain ratio of residues having a biphenyl structure with a mesogen skeleton that is easy to self-align as the diamine residue and the acid anhydride residue that constitute the polyamic acid. Therefore, the polyimide composition formed by imidizing the polyamic acid composition can realize a highly ordered crystalline structure without significantly decreasing the adhesion to a metal layer such as a copper foil, thereby making it possible to reduce the dielectric loss tangent. Moreover, it is possible to increase the thermal conductivity because the phonon scattering can be reduced.
[0014] The polyamic acid composition of the present invention employs, as a thermally conductive filler, α-alumina fine particles having high crystallinity and low dielectric tangent within a predetermined particle size range. This makes it possible to improve the thermal conductivity of a polyimide composition formed by imidizing a polyamic acid composition without increasing the dielectric tangent value. Moreover, by dispersing α-alumina fine particles in a predetermined amount range in the polyamic acid, it becomes possible to impart good coatability to the polyamic acid composition with suppressed aggregation of the α-alumina fine particles, and it becomes possible to prevent a significant decrease in adhesion to a metal layer such as a copper foil.
[0015] Therefore, the polyimide composition formed from the polyamic acid composition of the present invention is applicable to high-density mounting and can be suitably used as a material for manufacturing electronic parts such as FPCs that require high-speed signal transmission and high reliability. Furthermore, a metal-clad laminate using the polyimide composition can be applied to circuit boards such as FPCs that transmit high-frequency signals of, for example, 10 GHz or more. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described.
[0017] [Polyamic acid composition] The polyamic acid composition of the present invention contains polyamic acid and α-alumina fine particles. The polyamic acid and the α-alumina fine particles will be described below.
[0018] <Polyamic acid> The polyamic acid constituting the polyamic acid composition of the present invention has a diamine residue derived from the diamine component and an acid anhydride residue derived from the tetracarboxylic dianhydride component, and is converted to a polyimide by a conventional imidization treatment. (Diamine residue)
[0019] The diamine residue derived from the diamine component has a biphenyl structure in which two benzene rings are bonded by a single bond. This diamine residue has a rigid biphenyl structure, so it has the effect of imparting an ordered structure to the polyimide. This makes it possible to lower the dielectric tangent of the polyimide, and also imparts low gas permeability and good long-term heat-resistant adhesion to the polyimide.
[0020] The diamine component which induces the diamine residue having a biphenyl structure has a biphenyl structure and has one amino group on each benzene ring. In addition, as long as the effect of the present invention is not impaired, there is no limitation on the bonding position of the amino group, and other substituents such as alkyl groups and aryl groups may also be present. Examples of such diamine components include 2,2'-diaminobiphenyl, 3,3'-diaminobiphenyl, 4,4'-diaminobiphenyl, 1,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 3,3'-dimethyl-4,4'-diaminobiphenyl, and 2,2'-n-propyl-4,4'-diaminobiphenyl (m-NPB). Among them, 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB) is preferred from the viewpoints of reducing the thermal expansion coefficient and forming a highly ordered crystalline structure.
[0021] In the present invention, the diamine residue derived from the diamine component contains 10 mol % or more, preferably 15 mol % or more, of a diamine residue having a biphenyl structure. It may contain 100 mol %. If it is less than 10 mol %, it may be difficult to reduce the dielectric tangent of the polyimide.
[0022] In the present invention, the diamine residue derived from the diamine component may contain a diamine residue derived from a known diamine compound not having a biphenyl structure, within the range not impairing the effects of the present invention. Examples of such known diamine compounds include 1,4-diaminobenzene (p-PDA: paraphenylenediamine), 4-aminophenyl-4'-aminobenzoate (APAB), 3,3'-diaminodiphenylmethane, 3,3'-diaminodiphenylpropane, 3,3'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 3,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylpropane, 3,4'-diaminodiphenyl sulfide, 3,3'-diaminobenzophenone, (3,3'-bisamino)diphenylamine, 1,4-bis(3-aminophenoxy)benzene, 3-[4-(4-aminophenoxy)phenoxy]benzeneamine, 3-[3-(4-aminophenoxy)phenoxy]benzeneamine, 1,3-bis(4- aminophenoxy)benzene (TPE-R), 1,3-bis(3-aminophenoxy)benzene (APB), 4,4′-[2-methyl-(1,3-phenylene)bisoxy]bisaniline, 4,4′-[4-methyl-(1,3-phenylene)bisoxy]bisaniline, 4,4′-[5-methyl-(1,3-phenylene)bisoxy]bisaniline, bis[4,4′-(3-aminophenoxy)]benzanilide, 4-[3-[4- (4-aminophenoxy)phenoxy]phenoxy]aniline, 4,4′-[oxybis(3,1-phenyleneoxy)]bisaniline, bis[4-(4-aminophenoxy)phenyl]ether (BAPE), bis[4-(4-aminophenoxy)phenyl]sulfone (BAPS), bis[4-(4-aminophenoxy)phenyl]ketone (BAPK), 2,2-bis-[4-(3-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), bis[4-(3-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]methane, bis[4-(3-aminophenoxy)phenyl]ether, bis[4-(3-aminophenoxy)]benzophenone, 9,9-bis[4-(3-aminophenoxy)phenyl]fluorene, 2,2-bis-[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis-[4-(3-aminophenoxy)phenyl]hexafluoro Propane, 4,4′-methylenedi-o-toluidine, 4,4′-methylenedi-2,6-xylidine, 4,4′-methylene-2,6-diethylaniline, 3,3′-diaminodiphenylethane, 3,3′-dimethoxybenzidine, 3,3′′-diamino-p-terphenyl, 4,4′-[1,4-phenylenebis(1-methylethylidene)]bisaniline, 4,4′-[1,3-phenylenebis(1-methylethylidene)]bisaniline, bis(p-aminocyclohexyl)methane, bis(p-β-amino-t-butylphenyl)ether, bis(p- β-methyl-δ-aminopentyl)benzene, p-bis(2-methyl-4-aminopentyl)benzene, p-bis(1,1-dimethyl-5-aminopentyl)benzene, 1,5-diaminonaphthalene, 2,6-diaminonaphthalene, 2,4-bis(β-amino-t-butyl)toluene, 2,4-diaminotoluene, m-xylene-2,5-diamine, p-xylene-2,5-diamine, m-xylylenediamine, p-xylylenediamine, 2,6-diaminopyridine, 2,5-diaminopyridine, 2,5-diamino-1,3,4-oxadiazole, Piperazine, 2'-methoxy-4,4'-diaminobenzanilide, 4,4'-diaminobenzanilide, 1,3-bis[2-(4-aminophenyl)-2-propyl]benzene, 1,4-bis[2-(4-aminophenyl)-2-propyl]benzene, 1,4-bis(4-aminophenoxy)-2,5-di-tert-butylbenzene, 6-amino-2-(4-aminophenoxy)benzoxazole, 2,6-diamino-3,5-diethyltoluene, 2,4-diamino-3,5-diethyltoluene, 2,4-diamino-3,3'-diethyl-5,Examples of the diamine compounds include aromatic diamine compounds such as 5'-dimethyldiphenylmethane and bis(4-amino-3-ethyl-5-methylphenyl)methane, and aliphatic diamine compounds such as dimer acid type diamines in which the two terminal carboxylic acid groups of a dimer acid are substituted with primary aminomethyl groups or amino groups.
[0023] As a preferred known diamine compound not having a biphenyl structure, 1,3-bis(4-aminophenoxy)benzene (TPE-R) and 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) can be mentioned from the viewpoint of improving the flexibility of the polyimide molecular chain and the adhesion to the copper foil. Therefore, it is preferable that the diamine residue derived from the diamine component contains 10 to 100 mol% of the diamine residue derived from 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB) and 0 to 90 mol% of the diamine residue derived from 1,3-bis(4-aminophenoxy)benzene (TPE-R) or 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP).
[0024] (Tetracarboxylic acid dianhydride component) The acid anhydride residue derived from the tetracarboxylic dianhydride component has a biphenyl structure in which two benzene rings are bonded by a single bond. This acid anhydride residue has a rigid biphenyl structure, and therefore has the effect of imparting an ordered structure to the polyimide. This makes it possible to lower the dielectric tangent of the polyimide, and also imparts low gas permeability and good long-term heat-resistant adhesion to the polyimide.
[0025] The tetracarboxylic dianhydride component which induces the acid anhydride residue having a biphenyl structure has a biphenyl structure and has a dicarboxylic anhydride residue on each benzene ring. In addition, as long as the effect of the present invention is not impaired, there is no limitation on the bonding position of the dicarboxylic anhydride residue, and other substituents such as alkyl groups and aryl groups may also be present. Examples of such tetracarboxylic dianhydride components include 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, and 2,2',3,3'-biphenyltetracarboxylic dianhydride. Among them, 3,3',4,4'-biphenyltetracarboxylic dianhydride is preferred from the viewpoint of low dielectric tangent and high thermal conductivity due to the formation of a highly ordered crystalline structure.
[0026] In the present invention, the acid anhydride residue derived from the tetracarboxylic dianhydride component contains 50 mol % or more, preferably 60 mol % or more, of an acid anhydride residue having a biphenyl structure. It may contain 100 mol %. If it is less than 50 mol %, it may be difficult to reduce the dielectric tangent of the polyimide.
[0027] In the present invention, the acid anhydride residue derived from the tetracarboxylic dianhydride component may contain an acid anhydride residue derived from a known acid dianhydride not having a biphenyl structure, within a range not impairing the effects of the present invention. Examples of such known acid dianhydrides include 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 4,4'-oxydiphthalic dianhydride, 2,2',3,3'-, 2,3,3',4'- or 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,3',3,4'-diphenylethertetracarboxylic dianhydride, bis(2,3-dicarboxyphenyl)ether acid dianhydride, 3,3'',4,4''-, 2,3,3'',4''- or 2,2'',3,3''-p-terphenyltetracarboxylic dianhydride, 2,2-bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride, ...4-dicarboxyphenyl)methane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3- or 3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7,8-, 1,2,6,7- or 1,2,9,10-phenanthrene-tetracarboxylic dianhydride, 2,3,6,7-anthracene tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydride, 2,3,5,6-cyclohexanoic dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 1,2,5,6-naphthalene tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic dianhydride, 2,6- or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8-)tetrachloronaphthalene-1,4,5,8-(or 2,3,6,7-)tetracarboxylic dianhydride, 2,3,8,9-, 3,4,9,10-, 4,5,10,11- or 5,6,11,12-perylene-tetracarboxylic dianhydride, cyclopentane-1,2,3, 4-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, etc.
[0028] A preferred known tetracarboxylic dianhydride that does not have a biphenyl structure is pyromellitic dianhydride from the viewpoint of reducing the thermal expansion coefficient. Therefore, the acid anhydride residue derived from the tetracarboxylic dianhydride component preferably contains 50 to 100 mol% of the acid anhydride residue derived from 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and 0 to 50 mol% of the acid anhydride residue derived from pyromellitic dianhydride (PMDA).
[0029] <α-alumina fine particles> The polyamic acid composition of the present invention contains α-alumina fine particles as a thermally conductive filler. α-alumina fine particles have the properties of high crystallinity and low dielectric tangent. Therefore, by using α-alumina fine particles as a thermally conductive filler, it is possible to improve the thermal conductivity of the polyimide containing the α-alumina fine particles without increasing the dielectric tangent. Commercially available products can be used as the α-alumina fine particles.
[0030] The average particle diameter of the α-alumina fine particles is 2 μm to 10 μm, preferably 2 μm to 5 μm. If the average particle diameter is too small, the effect of improving thermal conductivity will be small, and if it is too large, it will be difficult to disperse in the polyamic acid, and when a resin film is formed, voids may occur due to increased stress caused by peripheral resin shrinkage, which may make it difficult to control the effects of the invention. In addition, if the average particle diameter is too large, the particle diameter approaches the wavelength of the high frequency band, which affects the dielectric properties. Here, the average particle diameter is the average particle diameter D at which the cumulative value in the frequency distribution curve obtained by volume-based particle size distribution measurement using the laser diffraction scattering method becomes 50%. 50 It is.
[0031] The maximum particle size of the α-alumina fine particles is preferably not more than 15 μm, because if the maximum particle size exceeds 15 μm, the surface smoothness of the polyimide film decreases, the surface becomes easily uneven, and voids tend to occur at the interface between the α-alumina fine particles and the polyimide.
[0032] Furthermore, if the content of α-alumina fine particles in the polyamic acid composition is too low, the thermal conductivity properties will be low and sufficient properties as a heat dissipation material will not be obtained, while if the content is too high, not only will the polyimide composition become brittle and difficult to handle, but also the viscosity of the polyamic acid composition will increase when attempting to form a resin film, decreasing workability. Therefore, the content is 20 to 80 parts by volume, and preferably 30 to 70 parts by volume, per 100 parts by volume of polyamic acid.
[0033] <Other ingredients> The polyamic acid composition of the present invention may contain an organic solvent. Examples of the organic solvent include N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), N,N-diethylacetamide, N-methyl-2-pyrrolidone (NMP), 2-butanone, dimethylsulfoxide (DMSO), hexamethylphosphoramide, N-methylcaprolactam, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, and cresol. Two or more of these solvents may be used in combination, and aromatic hydrocarbons such as xylene and toluene may also be used in combination. The content of the organic solvent is not particularly limited, but it is preferable to adjust the amount of use so that the concentration of the polyamic acid is about 5 to 30% by weight.
[0034] Furthermore, the polyamic acid composition of the present invention may contain additives other than α-alumina fine particles, as necessary, within the scope of the effects of the invention, such as inorganic fillers such as silicon dioxide, magnesium oxide, beryllium oxide, boron nitride, aluminum nitride, silicon nitride, aluminum fluoride, and calcium fluoride, organic fillers such as fluorine-based polymer particles and liquid crystal polymer particles, plasticizers, curing accelerators, coupling agents, fillers, pigments, and flame retardants.
[0035] <Viscosity of Polyamic Acid Composition> The viscosity of the polyamic acid composition of the present invention is in a range that improves the handleability during coating and facilitates the formation of a coating film of uniform thickness, and is preferably in the range of, for example, 5,000 cps to 100,000 cps, and more preferably in the range of 10,000 cps to 50,000 cps.
[0036] <Preparation of Polyamic Acid Composition> The polyamic acid composition of the present invention can be prepared, for example, by mixing a diamine component and a tetracarboxylic dianhydride component in a solvent in a molar ratio of approximately 1:1, reacting them at a temperature of 0 to 100°C for 0.5 to 24 hours to prepare a polyamic acid solution, and mixing and dispersing α-alumina fine particles in the solution according to a conventional method.
[0037] [Polyimide composition] The polyimide composition of the present invention is obtained by subjecting the polyamic acid in the polyamic acid composition of the present invention to an imidization treatment in accordance with a conventional method, and can be characterized by the invention-specifying features described with respect to the polyamic acid composition of the present invention.
[0038] That is, the polyimide composition of the present invention is a polyimide composition containing a polyimide having a diamine residue derived from a diamine component and an acid anhydride residue derived from a tetracarboxylic dianhydride component, and α-alumina fine particles, the content of the α-alumina fine particles in the polyimide composition is 20 to 80 parts by volume per 100 parts by volume of polyimide; Average particle size of α-alumina particles D 50 is 2 μm or more and 10 μm or less (wherein the average particle diameter D 50 is the average particle size at which the cumulative value in the frequency distribution curve obtained by volume-based particle size distribution measurement using the laser diffraction scattering method is 50%, the diamine residue derived from the diamine component contains 10 mol % or more of a diamine residue having a biphenyl structure, The polyimide composition contains 50 mol % or more of acid anhydride residues derived from a tetracarboxylic dianhydride component that have a biphenyl structure.
[0039] The polyimide composition of the present invention having the above-mentioned constitution exhibits good thermal conductivity while maintaining the low dielectric properties of polyimide, and also exhibits a desired "coefficient of thermal expansion" and "good adhesion to metal layers" such as copper foil.
[0040] The weight average molecular weight of the polyimide composition of the present invention is preferably within the range of 10,000 to 400,000, and more preferably within the range of 50,000 to 350,000. If the weight average molecular weight is less than 10,000, the strength of the film tends to decrease and become brittle. On the other hand, if the weight average molecular weight exceeds 400,000, the viscosity increases excessively, and defects such as uneven film thickness and streaks tend to occur during coating. In addition, the glass transition temperature of the polyimide composition is preferably 300°C or higher from the viewpoint of imparting heat resistance. In order to make the glass transition temperature 300°C or higher, it is possible to appropriately select the tetracarboxylic dianhydride component and the diamine component for constituting the polyimide.
[0041] The form of the polyimide composition of the present invention is not particularly limited, but is preferably in the form of a film (sheet). In this case, it becomes a "resin film" having a single or multiple polyimide layers, and at least one of the polyimide layers should be a thermally conductive polyimide layer made of the polyimide composition of the present invention.
[0042] In other words, the "resin film" may be composed of only a thermally conductive polyimide layer formed from the polyamic acid composition of the present invention containing α-alumina fine particles, or may further have a polyimide layer that does not contain α-alumina fine particles. When the "resin film" has a laminated structure of multiple layers, it is preferable that all layers are formed from thermally conductive polyimide layers formed from the polyamic acid composition of the present invention in consideration of thermal conductivity. However, by making the adjacent layer of the thermally conductive polyimide layer containing α-alumina fine particles a layer that does not contain a thermally conductive filler such as α-alumina fine particles or a layer with a low content of such a filler, it is possible to obtain an advantageous effect of preventing the thermally conductive filler from slipping off during processing, etc. When the polyimide layer does not contain a thermally conductive filler, the thickness of the layer is, for example, within the range of 1 / 100 to 1 / 2, preferably 1 / 20 to 1 / 3, of the thermally conductive polyimide layer containing α-alumina fine particles. In the case where a polyimide layer that does not contain a thermally conductive filler is provided, by placing the polyimide layer in contact with a metal layer, it is expected that the adhesion between the polyimide layer and the metal layer will be improved.
[0043] In such a "resin film", the thickness of the thermally conductive polyimide layer formed from the polyimide composition of the present invention is preferably within the range of 2 to 100 μm, and more preferably within the range of 4 to 50 μm. In addition, the maximum particle size of the α-alumina fine particles is preferably within the range of 0.05 to 0.7 relative to the thickness of the thermally conductive polyimide layer. If the maximum particle size of the α-alumina fine particles is less than 0.05 relative to the thickness of the thermally conductive polyimide layer, there is a concern that the thermal conductivity will be insufficient, and if it exceeds 0.7, there is a concern that the smoothness of the surface of the thermally conductive polyimide layer will be impaired.
[0044] The overall thickness of such a "resin film" is preferably within the range of 2 to 100 μm, and more preferably within the range of 4 to 50 μm. If the thickness of the "resin film" is less than 2 μm, problems such as wrinkles in the metal foil during the transport process during the manufacture of the metal-clad laminate are likely to occur. On the other hand, if the thickness of the "resin film" exceeds 100 μm, it tends to be disadvantageous in terms of high thermal conductivity and flexibility. In addition, it is preferable that the withstand voltage of the "resin film" is 1 kV or more.
[0045] When the polyimide composition of the present invention is applied as, for example, an adhesive layer of a circuit board, it is preferable that the dielectric loss tangent (Tan δ:Df) at 10 GHz is 0.005 or less. If the dielectric loss tangent at 10 GHz exceeds 0.005, when the composition is used in a circuit board such as an FPC, problems such as loss of electrical signals tend to occur on the transmission path of high-frequency signals. The lower limit of the dielectric loss tangent at 10 GHz is not particularly limited.
[0046] Furthermore, when the polyimide composition of the present invention is applied, for example, as an adhesive layer for a circuit board, in order to ensure impedance matching, it is preferable that the product of the square root of the relative dielectric constant (Dk) and the dielectric loss tangent (Df) at 10 GHz, i.e., the E value, which is an index showing the dielectric properties calculated based on the following formula (1), is 0.35 or less, preferably 0.30 or less, and more preferably 0.25 or less. If the E value exceeds the above upper limit, problems such as loss of electrical signals are likely to occur on the transmission path of high-frequency signals when the composition is used in a circuit board such as an FPC.
[0047]
number
[0048] In addition, the coefficient of thermal expansion (CTE) of the polyimide composition of the present invention in the form of a film is preferably 5×10 or less, since if the coefficient of thermal expansion is too small, curling is likely to occur after the composition is made into a metal-clad laminate, resulting in poor handling properties, whereas if the coefficient of thermal expansion is too large, the dimensional stability as an electronic material such as a flexible substrate is reduced, and the heat resistance also tends to decrease.-6 ~30×10 -6 / K (5 to 30 ppm / K), more preferably 10 × 10 -6 ~25×10 -6 / K (10 to 25 ppm / K).
[0049] The thermal conductivity (λz) in the thickness direction of the polyimide composition of the present invention in the form of a film is preferably 0.5 W / mK or more, more preferably 1.0 W / mK or more, and particularly preferably 1.5 W / mK or more, since if the thermal conductivity λz is too low, it becomes difficult to apply it to heat dissipation applications. In addition, if the thermal conductivity λz is high, excellent heat dissipation properties can be obtained, and the resin film can be applied to many applications, such as heat dissipation substrates. In addition, the thermal conductivity (λz) of the resin film is preferably 1.0 W / mK or more in the planar direction, and more preferably 2.0 W / mK or more.
[0050] <Preparation of Polyimide Composition (Formation of Thermally Conductive Polyimide Layer)> The method for preparing the polyimide composition in the form of a thermally conductive polyimide layer from the polyamic acid composition of the present invention is not particularly limited, and any known method can be adopted. Here, the most typical example will be shown.
[0051] First, the polyamic acid composition of the present invention is directly cast onto any supporting substrate to form a coating film. Next, the coating film is dried at a temperature of 150°C or less to remove the solvent to a certain extent. Thereafter, the coating film is further heat-treated at a temperature range of 100 to 400°C, preferably 130 to 360°C, for about 5 to 30 minutes for imidization. In this way, a thermally conductive polyimide layer can be formed on the supporting substrate. When forming a polyimide layer having two or more layers, a resin solution of a first polyamic acid is applied and dried, and then a resin solution of a second polyamic acid is applied and dried. Thereafter, the resin solutions of polyamic acid are applied and dried in the same manner as necessary. Then, the polyimide layers are heat-treated at a temperature range of 100 to 400°C for about 5 to 30 minutes to perform imidization. If the heat treatment temperature is lower than 100°C, the dehydration ring-closing reaction of the polyimide does not proceed sufficiently, and conversely, if it exceeds 400°C, the polyimide layer may deteriorate.
[0052] <Metal-clad laminate> The metal-clad laminate of the present invention is characterized in that a metal layer and a polyimide insulating layer are laminated together, and the polyimide insulating layer is formed from the polyimide composition of the present invention. Also, a circuit board in which the metal layer of this metal-clad laminate is processed into wiring is also an embodiment of the present invention.
[0053] The polyimide insulating layer may be a multi-layer polyimide layer, in which case at least one layer of the multi-layer polyimide layer may be formed from the polyimide composition of the present invention. The metal-clad laminate may be a single-sided metal-clad laminate having a metal layer on only one side of the polyimide insulating layer, or a double-sided metal-clad laminate having metal layers on both sides.
[0054] In the metal-clad laminate of the present invention, the use of an adhesive for bonding the polyimide insulating layer and the metal layer is not excluded. When an adhesive layer is interposed in a double-sided metal-clad laminate having metal layers on both sides of a polyimide insulating layer, the thickness of the adhesive layer is preferably less than 30% of the thickness of the entire polyimide insulating layer, and more preferably less than 20%, so as not to impair thermal conductivity. When an adhesive layer is interposed in a single-sided metal-clad laminate having a metal layer on only one side of a polyimide insulating layer, the thickness of the adhesive layer is preferably less than 15% of the thickness of the entire polyimide insulating layer, and more preferably less than 10%, so as not to impair thermal conductivity. In order to configure the adhesive layer as a part of the polyimide insulating layer, it is preferable to form it from polyimide.
[0055] <Metal layer> The material of the metal layer of the component of the metal-clad laminate of the present invention is not particularly limited, and examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among these, copper or a copper alloy is particularly preferred. The metal layer may be made of a metal foil or may be a film on which metal has been vapor-deposited. In addition, since the resin composition can be directly applied, either a metal foil or a metal plate can be used, and copper foil or a copper plate is preferred.
[0056] The thickness of the metal layer is not particularly limited since it is appropriately set according to the purpose of use of the metal-clad laminate, but if it is too thin, problems such as wrinkles may occur during transportation in the manufacture of the metal-clad laminate, and if it is too thick, the metal layer becomes hard and the processability deteriorates, so it is preferably in the range of 5 μm to 3 mm, more preferably in the range of 12 μm to 1 mm. Regarding the thickness of the metal layer, a thick one is generally suitable for applications such as an in-vehicle circuit board, and a thin metal layer is generally suitable for applications such as an LED circuit board.
[0057] The method for producing the metal-clad laminate of the present invention can employ a known method. For example, a method of hot pressing a metal foil directly or via an arbitrary adhesive to a "resin film" including a thermally conductive polyimide film formed from the polyimide composition of the present invention, a method of forming a metal layer on a resin film by a method such as metal deposition, etc. can be mentioned. Note that the double-sided metal-clad laminate can be obtained, for example, by forming a single-sided metal-clad laminate, and then arranging the polyimide layers to face each other and pressing them together by hot pressing, or by pressing a metal foil onto the polyimide layer of the single-sided metal-clad laminate. EXAMPLES
[0058] The present invention will be described in detail below with reference to examples. The range is not limited to the above.
[0059] The abbreviations used in the examples represent the following compounds. m-TB: 2,2′-dimethyl-4,4′-diaminobiphenyl TPE-R: 1,3-bis(4-aminophenoxy)benzene BAPP: 2,2-bis(4-aminophenoxyphenyl)propane DAPE: 4,4′-diaminodiphenyl ether PMDA: Pyromellitic dianhydride BPDA: 3,3′,4,4′-biphenyltetracarboxylic dianhydride BTDA: 3,3′,4,4′-benzophenonetetracarboxylic dianhydride DMAc: N,N-dimethylacetamide Filler 1: Sumitomo Chemical Co., Ltd., product name: AA-3 (alumina, polyhedral sphere, true specific gravity: 3.98, D 50 :3.4μm, maximum particle size: 9μm, α rate: 99%) Filler 2: Sumitomo Chemical Co., Ltd., product name: AA-2 (alumina, polyhedral sphere, true specific gravity: 3.98, D 50 :2.1μm, maximum particle size: 8μm, alpha rate: 99%) Filler 3: Sumitomo Chemical Co., Ltd., product name: AA-1.5 (alumina, polyhedral sphere, true specific gravity: 3.98, D 50 :1.6μm, maximum particle size: 5μm, alpha rate: 99%) Filler 4: Sumitomo Chemical Co., Ltd., product name: AA-07 (alumina, polyhedral sphere, true specific gravity: 3.98, D 50 :0.83μm, maximum particle size: 5μm, alpha rate: 99%)
[0060] The properties evaluated in the examples were evaluated according to the following evaluation methods.
[0061] [Viscosity measurement] The viscosity (250°C) of the polyamic acid solutions of Synthesis Examples 1 to 5 was measured using an E-type viscometer (Brookfield, product name: DV-II+Pro). The rotation speed was set so that the torque was 10% to 90%, and the viscosity was read when it stabilized 2 minutes after the start of the measurement.
[0062] [Measurement of copper foil peel strength] The copper foil layer of the copper-clad laminate prepared in each Example and Comparative Example was pattern-etched into a rectangular shape 1.0 mm wide and 180 mm long, and test pieces 20 mm wide and 200 mm long were cut out so that the pattern was in the center, and a 180° peel test was performed according to IPC-TM-650.2.4.19. From a practical standpoint, a peel strength of 1.0 kN / m or more was evaluated as good (○), and a peel strength of less than 1.0 kN / m was evaluated as poor (×).
[0063] [Measurement of thermal conductivity in the thickness direction (λz)] The copper foil of the copper-clad laminates prepared in each Example and Comparative Example was etched away to obtain a polyimide resin film, which was then cut into a size of 20 mm x 20 mm. The thermal diffusivity in the thickness direction was measured by the laser flash method using a xenon flash analyzer (NETZSCH, product name: LFA447 Nanoflash), and the specific heat was measured by DSC and the density was measured by the water displacement method. The thermal conductivity (W / m K) was calculated based on these results. For practical purposes, a thermal conductivity (W / m K) of 0.5 W / m K or more is desirable.
[0064] [Measurement of dielectric constant (Dk) and dielectric loss tangent (Df)] The relative permittivity (Dk) and dielectric loss tangent (Df) of the polyimide resin film obtained by etching away the copper foil of the copper-clad laminate prepared in each Example and Comparative Example were measured at a frequency of 10 GHz using a vector network analyzer (manufactured by Agilent, product name: E8363C) and a split post dielectric resonator (SPDR resonator). The polyimide resin film used in the measurement was left for 24 hours under the conditions of temperature: 24 to 26°C and humidity: 45 to 55%. In practical use, it is desirable that the dielectric loss tangent (Df) is 0.005 or less, and the E value (√Dk×Df), which is an index of dielectric properties, is 0.35 or less.
[0065] [Measurement of coefficient of thermal expansion (CTE)] The coefficient of thermal expansion (CTE) of the polyimide resin film (3 mm x 15 mm) obtained by etching off the copper foil of the copper-clad laminate prepared in each Example and Comparative Example was measured by a thermomechanical analysis (TMA) device. The measurement was performed by increasing the temperature from 30°C to 280°C at a heating rate of 10°C / min while applying a load of 5.0 g to the polyimide resin film, then decreasing the temperature from 250°C to 100°C, and measuring the elongation (linear expansion) of the polyimide resin film during the temperature decrease. In practice, the coefficient of thermal expansion (CTE) is preferably within the range of 10 ppm / K to 30 ppm / K.
[0066] [Measurement of average particle size] Average particle size of α-alumina particles D 50 The particle size distribution was measured by a laser diffraction particle size distribution analyzer (Malvern Panalytical, product name: Master Sizer 3000) using water as the dispersion medium and a laser diffraction / scattering measurement method.
[0067] (Synthesis Example 1: Preparation of polyamic acid solution A) Under a nitrogen stream, m-TB (3.17 g, 0.0149 mol) and TPE-R (19.90 g, 0.0680 mol) were dissolved in 255 g of DMAc solvent in a 500 ml separable flask while stirring. PMDA (6.25 g, 0.0287 mol) and BPDA (15.68 g, 0.0532 mol) were then added. The solution was then stirred at room temperature for 3 hours to carry out a polymerization reaction, yielding a pale yellow viscous polyamic acid solution A.
[0068] (Synthesis Examples 2 to 5: Preparation of Polyamic Acid Solutions B to E) In the same manner as in Synthesis Example 1, the diamines and acid dianhydrides shown in Table 1 were added to carry out a polymerization reaction, thereby obtaining viscous polyamic acid solutions B to E.
[0069] [Table 1]
[0070] [Example 1] 56.7 g of the polyamic acid solution A and 23.3 g of the filler 1 were mixed uniformly using a centrifugal mixer to obtain a polyamic acid composition 1 (content of the filler relative to the polyamic acid: 50% by volume). The composition of the polyamic acid composition 1 is shown in Table 2.
[0071] Polyamic acid composition 1 was applied onto copper foil 1 (electrolytic copper foil, thickness: 35 μm, Rz=1.4 μm) so that the thickness after curing would be 15 μm, and the coating was dried by heating at 130° C. to remove the solvent. Then, a stepwise heat treatment was performed from 130 to 360° C. to complete imidization, and copper-clad laminate 1 was produced. The copper foil was removed from the obtained copper-clad laminate 1 by etching, to produce resin film 1. The evaluation results of resin film 1 are shown in Table 3.
[0072] [Example 2] 56.7 g of the polyamic acid solution B and 23.3 g of the filler 1 were mixed uniformly using a centrifugal mixer to obtain a polyamic acid composition 2 (content of the filler relative to the polyamic acid: 50% by volume). The composition of the polyamic acid composition 2 is shown in Table 2.
[0073] In the same manner as in Example 1, polyamic acid composition 2 was applied so that the thickness after curing would be 18 μm, a copper-clad laminate 2 was produced, and further a resin film 2 was produced. The evaluation results of resin film 2 are shown in Table 3.
[0074] [Example 3] 56.7 g of the polyamic acid solution C and 23.3 g of the filler 2 were mixed uniformly using a centrifugal mixer to obtain a polyamic acid composition 3 (content of the filler relative to the polyamic acid: 50% by volume). The composition of the polyamic acid composition 3 is shown in Table 2.
[0075] In the same manner as in Example 1, polyamic acid composition 3 was applied so as to have a thickness of 18 μm after curing to prepare copper-clad laminate 3, and further prepared resin film 3. The evaluation results of resin film 3 are shown in Table 3.
[0076] [Example 4] 56.7 g of polyamic acid solution A, 12.8 g of filler 1, and 10.5 g of filler 2 were mixed uniformly using a centrifugal mixer to obtain polyamic acid composition 4 (content of filler relative to polyamic acid: 50% by volume). The composition of polyamic acid composition 4 is shown in Table 2.
[0077] In the same manner as in Example 1, polyamic acid composition 4 was applied so as to give a thickness of 15 μm after curing to prepare copper-clad laminate 4, and further prepared resin film 4. The evaluation results of resin film 4 are shown in Table 3.
[0078] [Example 5] 40.8 g of polyamic acid solution A, 23.5 g of filler 1, and 15.7 g of filler 3 were mixed uniformly using a centrifugal mixer to obtain polyamic acid composition 5 (content of filler relative to polyamic acid: 70% by volume). The composition of polyamic acid composition 5 is shown in Table 2.
[0079] In the same manner as in Example 1, polyamic acid composition 5 was applied so as to give a thickness of 15 μm after curing to prepare copper-clad laminate 5, and further prepared resin film 5. The evaluation results of resin film 5 are shown in Table 3.
[0080] [Example 6] 72.5 g of the polyamic acid solution B and 7.5 g of the filler 1 were mixed uniformly using a centrifugal mixer to obtain a polyamic acid composition 6 (content of the filler relative to the polyamic acid: 20% by volume). The composition of the polyamic acid composition 6 is shown in Table 2.
[0081] In the same manner as in Example 1, polyamic acid composition 6 was applied so that the thickness after curing would be 18 μm, to prepare copper-clad laminate 6, and further prepare resin film 6. The evaluation results of resin film 6 are shown in Table 3.
[0082] [Example 7] On the copper foil 1, the polyamic acid solution A obtained in Synthesis Example 1 was applied so that the thickness after curing was 1.0 μm, and the solution was heated and dried at 120 ° C to remove the solvent. Next, the polyamic acid solution 1 was applied thereon so that the thickness after curing was 14 μm, and the solution was heated and dried at 90 to 140 ° C to remove the solvent. Further, the polyamic acid solution A obtained in Synthesis Example 1 was applied thereon so that the thickness after curing was 1.0 μm, and the solution was heated and dried at 120 ° C to remove the solvent. After that, the temperature was raised stepwise over 30 minutes in the temperature range of 130 to 360 ° C to produce a copper-clad laminate 7 consisting of three polyimide layers on the copper foil.
[0083] The copper foil of the copper-clad laminate 7 was removed by etching to prepare a resin film 7. The evaluation results of the resin film 7 are shown in Table 3.
[0084] [Example 8] On the copper foil 1, the polyamic acid solution A obtained in Synthesis Example 1 was applied so that the thickness after curing was 1.0 μm, and the solution was heated and dried at 120 ° C to remove the solvent. Next, the polyamic acid solution 5 was applied thereon so that the thickness after curing was 14 μm, and the solution was heated and dried at 90 to 140 ° C to remove the solvent. Further, the polyamic acid solution A obtained in Synthesis Example 1 was applied thereon so that the thickness after curing was 1.0 μm, and the solution was heated and dried at 120 ° C to remove the solvent. After that, the temperature was raised stepwise in the temperature range of 130 to 360 ° C over 30 minutes to produce a copper-clad laminate 8 consisting of three polyimide layers on the copper foil.
[0085] The copper foil of the copper-clad laminate 8 was removed by etching to prepare a resin film 8. The evaluation results of the resin film 8 are shown in Table 3.
[0086] Comparative Example 1 56.7 g of the polyamic acid solution D and 23.3 g of the filler 1 were mixed uniformly using a centrifugal mixer to obtain a polyamic acid composition 9 (content of the filler relative to the polyamic acid: 50% by volume). The composition of the polyamic acid composition 9 is shown in Table 2.
[0087] In the same manner as in Example 1, polyamic acid composition 9 was applied so as to give a thickness of 18 μm after curing to prepare copper-clad laminate 9, and further prepared resin film 9. The evaluation results of resin film 9 are shown in Table 3.
[0088] Comparative Example 2 56.7 g of the polyamic acid solution E and 23.3 g of the filler 1 were mixed uniformly using a centrifugal mixer to obtain a polyamic acid composition 10 (content of the filler relative to the polyamic acid: 50% by volume). The composition of the polyamic acid composition 10 is shown in Table 2.
[0089] In the same manner as in Example 1, the polyamic acid composition 10 was applied so as to have a thickness of 18 μm after curing to prepare a copper-clad laminate 10, and further a resin film 10 was prepared. The evaluation results of the resin film 10 are shown in Table 3.
[0090] Comparative Example 3 76.5 g of the polyamic acid solution C and 3.5 g of the filler 4 were mixed uniformly using a centrifugal mixer to obtain a polyamic acid composition 11 (content of the filler relative to the polyamic acid: 10% by volume). The composition of the polyamic acid composition 11 is shown in Table 2.
[0091] In the same manner as in Example 1, polyamic acid composition 11 was applied so that the thickness after curing would be 18 μm, to prepare copper-clad laminate 11, and further prepare resin film 11. The evaluation results of resin film 11 are shown in Table 3.
[0092] Comparative Example 4 40.8 g of the polyamic acid solution A, 23.5 g of the filler 3, and 15.7 g of the filler 4 were mixed in a centrifugal mixer, but the fillers aggregated and a resin film with a uniform thickness could not be formed.
[0093] [Table 2]
[0094] [Table 3]
[0095] <Discussion of Results> In the case of the polyamic acid compositions prepared in Examples 1 to 8, the content of the α-alumina fine particles in the polyamic acid composition was within the range of 20 to 80 parts by volume per 100 parts by volume of polyamic acid, and the average particle diameter D 50 is in the range of 2 μm to 10 μm, the diamine residues contain 10 mol % or more of diamine residues having a biphenyl structure, and the acid anhydride residues contain 50 mol % or more of acid anhydride residues having a biphenyl structure. Therefore, good results were obtained for all of the evaluation items of CTE, λz, peel strength, and dielectric properties.
[0096] On the other hand, in the case of Comparative Example 1, none of the diamine residues and acid anhydride residues constituting the polyamic acid of the polyamic acid composition contained a residue having a biphenyl structure, and in the case of Comparative Example 2, all of the diamine residues were diamine residues having a biphenyl structure, but all of the acid anhydride residues were acid anhydride residues derived from PMDA that did not have a biphenyl structure. Therefore, the Df value was 0.0071, which was significantly greater than 0.005, and the E value was 0.52, which was significantly greater than 0.35. In the case of Comparative Example 2, although the Df value was lower than that of Comparative Example 1, it still exceeded 0.005, and the E value was 0.46, which was greater than 0.35, and the peel strength was rated as "x".
[0097] In the case of Comparative Example 3, the α-alumina fine particles had an average particle diameter D 50 Because we used a material with a thickness of 0.83 μm, which is less than 2 μm, λz was less than 0.5 [W / m K], the thermal expansion coefficient was well above 30 [ppm / K], and the Df value exceeded 0.005.
[0098] In the case of Comparative Example 4, the α-alumina fine particles had an average particle diameter D 50 Since two types of polyamic acid having diameters of less than 2 μm, 1.6 μm (23.5 g) and 0.83 μm (15.7 g), were used in combination, aggregation occurred in the polyamic acid composition, making it impossible to apply the polyamic acid composition and thus impossible to produce a metal-clad laminate.
Claims
1. A polyamic acid composition comprising: a polyamic acid having a diamine residue derived from a diamine component and an acid anhydride residue derived from a tetracarboxylic dianhydride component; and α-alumina fine particles, the content of the α-alumina fine particles in the polyamic acid composition is 20 to 80 parts by volume per 100 parts by volume of the polyamic acid; Average particle size D of α-alumina particles 50 is 2 μm or more and 10 μm or less (wherein the average particle diameter D 50 is the average particle size at which the cumulative value in a frequency distribution curve obtained by volume-based particle size distribution measurement using a laser diffraction scattering method is 50%. the diamine residue derived from the diamine component contains 10 mol % or more of a diamine residue having a biphenyl structure, the acid anhydride residues derived from the tetracarboxylic dianhydride component contain 50 mol % or more of acid anhydride residues having a biphenyl structure; A polyamic acid composition which, when imidized to form a film, has a dielectric dissipation factor of 0.005 or less at 10 GHz and a thermal conductivity (λz) in the thickness direction of 0.5 W / mK or more.
2. 2. The polyamic acid composition according to claim 1, wherein the diamine residue having a biphenyl structure is a diamine residue derived from 2,2'-dimethyl-4,4'-diaminobiphenyl, and the acid anhydride residue having a biphenyl structure is an acid anhydride residue derived from 3,3',4,4'-biphenyltetracarboxylic dianhydride.
3. the diamine residue derived from the diamine component contains 10 to 100 mol % of a diamine residue derived from 2,2'-dimethyl-4,4'-diaminobiphenyl and 0 to 90 mol % of a diamine residue derived from 1,3-bis(4-aminophenoxy)benzene or 2,2-bis[4-(4-aminophenoxy)phenyl]propane; The polyamic acid composition according to claim 1, wherein the acid anhydride residues derived from the tetracarboxylic dianhydride component contain 50 to 100 mol % of acid anhydride residues derived from 3,3',4,4'-biphenyltetracarboxylic dianhydride and 0 to 50 mol % of acid anhydride residues derived from pyromellitic dianhydride.
4. A polyimide composition comprising: a polyimide having a diamine residue derived from a diamine component and an acid anhydride residue derived from a tetracarboxylic dianhydride component; and α-alumina fine particles, the content of the α-alumina fine particles in the polyimide composition is 20 to 80 parts by volume per 100 parts by volume of polyimide; Average particle size D of α-alumina particles 50 is 2 μm or more and 10 μm or less (wherein the average particle diameter D 50 is the average particle size at which the cumulative value in a frequency distribution curve obtained by volume-based particle size distribution measurement using a laser diffraction scattering method is 50%. the diamine residue derived from the diamine component contains 10 mol % or more of a diamine residue having a biphenyl structure, the acid anhydride residues derived from the tetracarboxylic dianhydride component contain 50 mol % or more of acid anhydride residues having a biphenyl structure; A polyimide composition having, in a film state, a dielectric dissipation factor at 10 GHz of 0.005 or less and a thermal conductivity (λz) in the thickness direction of 0.5 W / mK or more.
5. 5. A metal-clad laminate comprising a metal layer and a polyimide insulating layer laminated together, the polyimide insulating layer being formed from the polyimide composition according to claim 4.
6. A circuit board, in which the metal layer of the metal-clad laminate of claim 5 is processed into wiring.
Citation Information
Patent Citations
Laminate used for flexible substrate and its manufacturing method
JP2008251900A
Polyamic acid and non-thermoplastic polyimide resin
JP2010053322A
Thermally conductive resin composition, and laminate using the same
JP2014177559A
Polyimide, resin film, and metal-clad laminate
WO2014208644A1
Polyamide acid, thermoplastic polyimide, resin film, metal-clad laminate and circuit board
WO2017159274A1